Estudo da migração de ftalatos e bisfenol A para a saliva em procedimentos odontológicos - José Messias Gomes (2020)
Phthalates and bisphenol A are Endocrine Disrupting Chemicals (EDCs) widely used as plasticizers in several products, including materials used in dental procedures. Exposure to these compounds is associated with dysfunctions in the endocrine system even at low concentrations. Analytical techniques have been developed and applied to evaluate the migration of EDCs from different materials. Hollow Fiber Liquid-Phase Microextraction (HF-LPME) was used in this study to extract dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), diisobutyl phthalate (DiBP), Di (2-Ethylhexyl) phthalate (DEHP) and bisphenol A (BPA) from human saliva samples. Their concentrations were obtained using gas chromatography coupled to mass spectrometry (GC/MS). To analyze BPA using the GC/MS technique, it was necessary to derivatize the samples with BSTFA. The optimization of the extraction step was evaluated with three solvents: octanol, ethyl octanoate and a mixture of these solvents in a 1:1 v/v ratio. The solvent mixture showed better performance in extracting the analytes. The effect of the pH of the donor phase on the extraction of the analytes was also evaluated. The pH influenced the extraction of DMP and DEHP, which showed greater efficiency in neutral medium. The method used for the analysis of phthalates and BPA in saliva was validated in artificial saliva and presented good results of selectivity, linearity (R2> 0.95), low detection limits (0.36–1.97 µg L-1) and quantification (0.66–6.56 µg L-1). The recovery varied between 80 and 125% while the variation in enrichment was between 480 and 750%. This method was applied to the analysis of sixty saliva samples collected from twenty children who underwent dental procedures to correct open bite. The samples were collected in three stages, before the dental procedure, thirty minutes and twenty-four hours after the dental procedure. DMP and DEP analytes were not detected in any of the analyzed samples. DiBP and BPA had a higher concentration thirty minutes after dental procedures. The Principal Component Analysis (PCA) of the saliva samples was performed and the formation of two clusters (A and B) with separation in PC2 was observed, both groups contain samples collected at all times. The results show that DBP and DiBP are in higher concentration in group A, while BPA is in lower concentration in the samples that form group B. The analysis of variance (ANOVA) revealed significant differences in the average concentration of DiBP and BPA for different times studied. For DiBP, significant differences in the concentration of this compound were found in samples collected before and thirty minutes after the dental procedure. And for BPA, these differences were found in samples collected thirty minutes and twenty-four hours after treatment. Based on the concentrations determined in that study, it was possible to Estimate the Daily Consumption (EDC) of each analyte and compare it with the tolerable daily intake (Tolerable Daily Intake - TDI) determined by the European Food Safety Authority (EFSA). For all analytes, the ECD values were below the TDI values, indicating that the migration of these compounds was at acceptable levels according to EFSA. The results obtained allow us to conclude that the HF-LPME-GC / MS method used was adequate to evaluate the migration of phthalates and BPA from dental materials to saliva. The HF-LPME method applied to saliva, in addition to being non-invasive, is practically solvent-free, which reduces the cost of extraction when compared to traditional techniques. As a perspective, this method may have its scope expanded to biomonitor other classes of toxic compounds in saliva.